Phytosequestration of Metals in Selected Plants Growing on a Contaminated Okhla Industrial Areas, Okhla, New Delhi, India - Anwar, Ahmad; Rumana, Ghufran; Zularisam, A. W. (Springer Netherlands, 2011)
Contamination of metal ions in soil and water represents more pressing threats to resources as well as human health. The present research was carried out to screen the phytosequester plants growing in industrial waste- and wastewater-affected industrial areas of Okhla, New Delhi, India. Accumulation trend of metal Fe, Zn, Cu, Cr, Pb, Cd, Hg, and As from soil and wastewater by plants were collected for study. Among aquatic plants Hydrilla verticillata, Marsilea quadrifolia, and Ipomea aquatica were found to be highest metals accumulator, Eclipta alba and Sesbania cannabina among terrestrial plant were highest accumulator of metals. Among the algal spp. Spirulina platensis and Phormidium papyraceum were the most efficient in accumulating Cd and Hg. The maximum bioconcentration factor (BCF) was recorded in Hygroryza aristata for the metals (Hg, Cd) in M. quadrifolia (Cd, Cr), in E. alba (Cr, Cu), and in S. platensis (Hg, Pb). However, the translocation factor (TF) of metals was found more in M. quadrifolia followed by I. aquatica than other plants. Among all the plants, H. verticillata showed high TF and low BCF values for toxic metals (Pb, Cr) and was suitable for phytostabilization of these metals. Our study showed that native plant species growing on contaminated sites may have a potential of phytosequestration of these metals.